Research on the Mechanism of Mannose Oligosaccharide Enhancing the Inhibitory Effect of Bifidobacterium breve on the Growth of Fusobacterium nucleatum - Xuyan ZHANG; Ruijie LIU; Bo ZHAO; Xiaoxi XU (Shipin gongye ke-ji)
To explore the synergistic inhibitory effect and mechanism of Bifidobacterium and oligosaccharides on Fusobacterium nucleatum, six common Bifidobacterium species (Bifidobacterium animalis, Bifidobacterium longum, Bifidobacterium infantis, Bifidobacterium breve, Bifidobacterium bifidum, Bifidobacterium youth) were used to metabolize six widely used oligosaccharides (mannose oligosaccharides, galactose oligosaccharides, isomaltose oligosaccharides, fructooligosaccharides, lactulose oligosaccharides, and arabinogalacia) with different structures. Through the generation of hydrogen sulfide and the inhibition of biofilm, the optimal combination of inhibition of Fusobacterium nucleatum was determined. The cell integrity of Fusobacterium nucleatum was analyzed by scanning electron microscopy, transmission electron microscopy and flow cytometry to study the inhibition mechanism of Fusobacterium nucleatum. The inhibitory effect of acidic metabolites on Fusobacterium nucleatum and the yield of short-chain fatty acids were investigated. In addition, the potential bacteriocin gene clusters of Bifidobacterium were also excavated. The results showed that mannose oligosaccharide had the best effect in promoting Bifidobacterium breve to inhibit Fusobacterium nucleatum, and the combination could significantly reduce the production of H2S and the formation of biofilm. Compared with the blank control, when the addition amount of cell-free supernatant reached 20%, the inhibition rate of Fusobacterium nucleatum could reach 63.16%±4.48%. The apparent structure was obviously damaged, protein and nucleic acid flowed out, and the integrity and permeability of the cell membrane were destroyed. This inhibitory effect diminished as the supernatant's pH became closer to neutral, suggesting that the supernatant's acidic metabolites were crucial to the antibacterial action. The supernatant had the following amounts of acid: 26.112 mmol/L for acetic acid, 10.829 mmol/L for propionic acid, 5.106 mmol/L for butyric acid, and 5.232 mmol/L for valeric acid. In addition, Bifidobacterium breve was predicted to contain two potential bacteriocin synthesis gene clusters. In conclusion, the combination of mannose oligosaccharides and Bifidobacterium breve may be used as a safe and effective biological control inhibitor of Fusobacterium nucleatum, which may provide a safer and more effective method for the prevention and adjuvant treatment of colorectal cancer and other tumor diseases.